RELATIONSHIP BETWEEN BODY IMAGE AND QUALITY OF LIFE IN CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS AT Dr. HARDJONO REGIONAL HOSPITAL PONOROGO - Agita Afrillia Putri; Ucik Ernawati (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Chronic renal failure (CKD) is a condition of progressive and permanent decline in kidney function. One of the main therapies is hemodialysis, which has an impact on significant physical changes and perceptions of body image and quality of life.This study aims to analyze the relationship between body image and quality of life of patients with GGK who undergo hemodialysis at Dr. Harjono Ponorogo Hospital. The study used a quantitative approach, correlational design, and cross-sectional method. A sample of 94 patients was selected using purposive sampling technique. The instruments used were MBRSQ questionnaire for body image and WHOQOL-BREF for quality of life. The results spearman test showed a significant relationship between body image and quality of life (r = 0.630; p < 0.001). Patients with positive body image tend to have better quality of life.Body image is an important factor in supporting the quality of life of patients with CKD. Psychosocial interventions are needed in nursing care to improve self-acceptance and positive body image.